Pendokumentasian dan Pembuatan Media Sosialiasi Pergelaran dan Festival di Desa Madiredo - Franciscus Apriwan; Kumoro, Nindyo Budi; Kadir, Hatib Abdul; Permatasari, Adila Sekar Aulia (Faculty of Cultural Studies, Universitas Brawijaya, 2024)
Abstract This community service project documents and develops socialization media for performances and festivals in Madiredo Village. Through collaboration between the village government, residents, and the community service team from Brawijaya University, various methods such as interviews, observations, and group discussions are used to design effective socialization strategies. The primary objective of this program is to increase community participation and ensure the sustainability of the village's cultural festival, while strengthening Madiredo's local identity. The results of this community service initiative highlight the importance of a collaborative approach in managing community-based cultural activities, with a focus on documentation and the creation of comprehensive informational media. Keywords: events; documentation; festival